GAMBARAN PELAYANAN SOSIAL LANJUT USIA DI SUMATERA BARAT - aris; Wiswinartin (Regalia: Jurnal Riset Gender dan Anak, 2022)
This research is a literature review that aims to describe how social services for the elderly in the West Sumatra study are. Institution-based elderly care in West Sumatra is carried out by the Tresna Werdha Social Panti (PSTW) which is managed by both the government and the private sector. Meanwhile, community based care for the elderly can be in the form of the Elderly Social Welfare Institution (LKS). Regarding household-based care for the elderly, it is a form of assistance and care for the elderly at home carried out by the nuclear family. The data analysis technique used is content analysis method. The data sources in this study were journals and articles on care for the elderly in Indonesia. The data presented is data in the form of words that require processing to be concise and systematic). While the writing instrument in this article is a checklist for the classification of writing materials, writing schemes/maps and the format of writing notes